A Plan-Do-Study-Act Approach to Improving Bowel Preparation Quality. (March 2017) - Calderwood, Audrey H.; Mahoney, Elaine M.; Jacobson, Brian C.
Up to 20% of patients presenting for colonoscopy have inadequate bowel cleanliness. In this study, the Plan-Do-Study-Act quality improvement process was used to improve bowel cleanliness among outpatients undergoing screening colonoscopy at Boston Medical Center. Rates of inadequate bowel cleanliness were assessed at baseline (April 2010 to September 2012), during several rapid-cycle experiments (October 2012 to September 2013), and through an observation phase (October 2013 to September 2015). The baseline rate of inadequate cleanliness was 9% with a target of 5%. Gap analysis identified 3 areas amenable to specific interventions: contacting patients, commitment to the procedure, and complexity and variation in instructions. Rates of inadequate cleanliness decreased to 4% at the end of the last intervention, but began rising for new reasons. Standardizing instructions and the use of navigators improved preparation quality. Bowel cleanliness is the end result of a multistep process with areas for improvement at many levels. Long-term monitoring is required to ensure ongoing success.